PENGARUH KETERAMPILAN MENGAJAR GURU EKONOMI DALAM MEMBERIKAN PENGUATAN TERHADAP MOTIVASI BELAJAR SISWA KELAS XI IPS DI SMA PGRI PEKANBARU - Hasbullah Hasan; Suarman '; RM. Riadi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated by the students who really need motivation in learning one of them that their skills provide reinforcement by the teacher for reinforcement is a tribute to the stimulation and enthusiasm in learning. Encouragement and spirit is what will influence student motivation in learning mainly on economic elajaran. However, in reality not all teachers are aware of the importance of giving reinforcement to students. Whereas if the honors can increase students' motivation for students to feel his efforts are well appreciated. The purpose of this study was to determine and analyze how much influence skills provide reinforcement to motivate students of class XI IPS SMA PGRI Pekanbaru. The population in this study were students of class XI IPS SMA PGRI Pekanbaru odd semester of 2016/2017 academic year with the number of 75 people. The sampling technique refers to the idea Arikunto (2006) which says that when the subject is less than 100 better taken all that research is the study population. Based on the analysis concluded that the significant value on the table Annova amounted to 0.078 greater than the critical value of 0.05. Then obtained 0.078 > 0.05, and these results show that the Skills Provide Reinforcement (KMP) has no significant effect on Student Motivation (MBS) students of class XI IPS SMA PGRI Pekanbaru. Judging from R Square of 0.042, this shows that the independent variables used in this study can only affect the dependent variable of 4.2%. Thus it can be said that the ability of independent variables in influencing the dependent variable is low. Based on the regression coefficient if Strengthening Skills Provide increased by 1, the Student Motivation will also be increased by 0.304.Key Words : Teacher’s skill in giving reinforcement, student’s motivation